2016
DOI: 10.1039/c5gc01301a
|View full text |Cite
|
Sign up to set email alerts
|

Novel astaxanthin extraction from Haematococcus pluvialis using cell permeabilising ionic liquids

Abstract: ARTICLE This journal isHaematococcus pluvialis (H. pluvialis) is a natural source of the food colorant astaxanthin. It is characterised by a thick resistant cell wall composed of a non-hydrolysable biopolymer, sporopollenin. High energy-consuming mechanical disruption is required to improve the extractability of astaxanthin. Opposed to that, this study uses a novel technology with ionic liquids (ILs) to permeabilise the Haematococcal cyst cell under mild conditions of temperature and improve the extraction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(72 citation statements)
references
References 33 publications
3
68
1
Order By: Relevance
“…Although microalgal cells contain several valuable biomolecules, the currently applied separation processes valorize only one specific product (e.g. astaxanthin, phycobiliproteins) . The development of efficient, mild and scalable methods/processes, capable of fractionating different microalgal biomolecules, is of particular importance .…”
Section: Introductionmentioning
confidence: 99%
“…Although microalgal cells contain several valuable biomolecules, the currently applied separation processes valorize only one specific product (e.g. astaxanthin, phycobiliproteins) . The development of efficient, mild and scalable methods/processes, capable of fractionating different microalgal biomolecules, is of particular importance .…”
Section: Introductionmentioning
confidence: 99%
“…Results regarding microscopy were in line with the findings of Desai et al . (). As compared to mature red‐coloured cysts (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…In a two-step pretreatment (HCl and USassisted acetone extraction), showed the best astaxanthin extraction yield (Dong et al, 2014). ILs are solely composed of loosely hold cations and anions characterised by negligible vapour pressure, low melting temperatures, and exceptional thermal and chemical stability, has been widely utilised for catalysis for biodiesel synthesis, removal of metal ions and biological reaction media (Desai et al, 2016). In addition, with the high capacity of dissolving cellulose, ILs appeared to be a novel cell disruption technique for lipid and protein recovery from C. vulgaris (Choi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although, the lipid recovery from C. vulgaris using ILs has been studied, few researchers have investigated the capability of ILs for disrupting the most resistant cell wall of H. pluvialis and enhancing the astaxanthin extraction, excepted the studies conducted by Desai et al . (), who found that cell wall of H. pluvialis was efficient disruption by 1‐Ethyl‐3‐methylimidazolium dibutylphosphate at mild temperature, and more than 70% astaxanthin was extracted. While Praveenkumar et al .…”
Section: Introductionmentioning
confidence: 97%
“…Orr et al (2016) have demonstrated that the complete hydrolysis of wet C. vulgaris cells using ILs for lipid recovery at room temperature with a great recyclability process. Although, the lipid recovery from C. vulgaris using ILs has been studied, few researchers have investigated the capability of ILs for disrupting the most resistant cell wall of H. pluvialis and enhancing the astaxanthin extraction, excepted the studies conducted by Desai et al (2016), who found that cell wall of H. pluvialis was efficient disruption by 1-Ethyl-3-methylimidazolium dibutylphosphate at mild temperature, and more than 70% astaxanthin was extracted. While Praveenkumar et al (2015) proposed a novel, energyefficient biological pre-treatment combining germination (12-18 h) of H. pluvialis with IL-based astaxanthin extraction.…”
Section: Introductionmentioning
confidence: 99%